Foreign Body in a Bitch - Removal with Gastrotomy and Enterotomy - Borges Resende, Sarah; Rodrigues da Silva , Pâmela; Mota Sousa , Lucas; Viana, Diego Carvalho (Acta Scientiae Veterinariae, 2024)
Background: Morphophysiology makes it possible to understand the entire organism of an animal, enabling the identification of abnormalities and alterations. In view of this, it is extremely important to understand the gastrointestinal system and the nutrition of companion animals, particularly dogs, as they tend to ingest inedible objects, which can result in changes in behavior and nutrition. The foreign body refers to objects that are resistant to digestion by hydrochloric acids, such as thread, stones, plastic, and bones. When animals are affected, they may show several symptoms such as vomiting, gastric distention, and intestinal obstruction. In addition, depending on the region and severity, surgical intervention may be required to remove the foreign body. The aim of this study was to describe a case of gastrointestinal obstruction in a bitch, as well as to address the established drug therapy and describe the surgical technique. Case: A 1-year-and-1-month-old Shih-Tzu bitch, weighing 5.6 kg, was initially treated at a veterinary clinic in Imperatriz, Maranhão. The bitch presented with lethargy and intermittent vomiting. On physical examination, ocular secretion and pain on abdominal palpation were observed, but the other parameters were within the normal range. Several tests were performed. In addition, the complete blood count showed alteration, indicating leukocytosis due to neutrophilia, together with monocytosis and eosinophilia. However, the biochemistry results were within normal limits, and the 4dx rapid test did not indicate any parasitic disease. Abdominal ultrasonography was decisive in confirming the diagnosis of a foreign body. The patient was referred to another veterinary clinic to undergo gastrostomy and enterotomy surgeries for the removal of foreign bodies. Moments before the surgery, due to the animal’s worsening condition with emesis, the surgery had to be initially interrupted. Afterwards, it was sent to the surgical center, where it underwent gastrostomy and enterotomy procedures to remove 3 round structures. In the postoperative period, he was followed up to monitor the parameters, with cases of hypoglycemia that were effectively managed through appropriate interventions. In the following days until the day of discharge, he showed significant improvement, returning 10 days later to the clinic to remove the stitches. Discussion: The habit of consuming foreign objects is common among small animals but tends to affect younger dogs, like the patient in this case. According to the literature, foreign body obstruction can generate different clinical signs according to the affected region. In this case, the dog only presented pain on palpation in the abdomen region, along with gastrointestinal distress. The treatment indicated for this case was surgical intervention, specifically gastrostomy and enterotomy procedures. The ultrasound examination played a crucial role in confirming the diagnosis by identifying abnormal structures present in the stomach and small intestine. Complementary tests were performed to complete the physical examination. During hospitalization to treat the clinical conditions of emesis, the drug therapy of choice was Omeprazole and Maropitant Citrate, and Buscofen (dipyrone and scopolamine). The animal showed improvement during the postoperative period and the monitoring of the clinical parameters allowed for better control of its condition. Keywords: obstruction, gastrointestinal, surgery.